Progressive Encephalomyelitis with Rigidity and Myoclonus Associated With Anti-GlyR Antibodies and Hodgkin’s Lymphoma: A Case Report - Borellini, Linda; Lanfranconi, Silvia; Bonato, Sara; Trezzi, Ilaria; Franco, Giulia; Torretta, Lorella; Bresolin, Nereo; Di Fonzo, Alessio Barnaba (Frontiers in Neurology, 2017)
Introduction: A 60-year-old man presented with a 6-month history of low back pain and progressive rigidity of the trunk and lower limbs, followed by pruritus, dysphonia, hyperhydrosis and urinary retention. Brain and spinal imaging were normal. EMG showed involuntary motor unit hyperactivity. Onconeural, anti-GAD, VGKC-complex and DPPX autoantibodies were negative. CSF was negative. Symptoms were partially responsive to baclofen, gabapentin and clonazepam, but he eventually developed severe dysphagia. Anti-GlyR antibodies turned out positive on both serum and CSF. A plasmapheresis cycle was completed with good clinical response. A PET scan highlighted an isolated metabolically active axillary lymphnode, that turned out to be a classic type Hodgkin lymphoma (HL), in the absence of bone marrow infiltration nor B symptoms. Polychemotherapy with ABVD protocol was completed with good clinical response and at one year follow up the neurological examination is normal. Background: Progressive encephalomyelitis with rigidity and myoclonus (PERM) is a rare and severe neurological syndrome characterized by muscular rigidity and spasms as well as brainstem and autonomic dysfunction. It can be associated with anti-glutamic acid decarboxylase (GAD), glycine receptor (GlyR) and dipeptidyl peptidase-like protein 6 (DPPX) antibodies. All of these autoantibodies may be variably associated to malignant tumours and their response to immunotherapy, as well as to tumour removal, is not easily predictable. Conclusion: PERM has already been described in association with HL, but this is the first case report of a HL manifesting as antiGlyR antibodies related PERM. Our report highlights the importance of malignancy screening in autoimmune syndromes of suspected paraneoplastic origin.